1998
DOI: 10.1002/(sici)1099-1050(199802)7:1<39::aid-hec323>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Health economic assessment of behavioural rehabilitation in chronic low back pain: a randomised clinical trial

Abstract: SUMMARYThe aim of this cost-effectiveness study was to compare a combined operant programme plus cognitive/relaxation programme with an operant programme plus attention-control and to compare both programmes with a waiting-list control group and with operant rehabilitation provided, as usual, by the same rehabilitation centre. One hundred and forty eight patients with chronic low back pain were randomly assigned to the different conditions. The economic endpoints were the costs of the programme and other healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 11 publications
1
41
0
2
Order By: Relevance
“…Hence, our findings suggest a significant effect from the incorporation of even a limited behavioral element. This comply with findings in chronic LBP patients treated conservatively [6,10,23,24]. On the other hand, a recent review of 12 RCTs by Guzman et al [8] concluded the existence of evidence for an intensive multidisciplinary rehabilitation but did not find evidence for a light multidisciplinary approach.…”
Section: Discussionsupporting
confidence: 74%
“…Hence, our findings suggest a significant effect from the incorporation of even a limited behavioral element. This comply with findings in chronic LBP patients treated conservatively [6,10,23,24]. On the other hand, a recent review of 12 RCTs by Guzman et al [8] concluded the existence of evidence for an intensive multidisciplinary rehabilitation but did not find evidence for a light multidisciplinary approach.…”
Section: Discussionsupporting
confidence: 74%
“…One study conducted a full economic evaluation of a behavioural treatment (Goossens et al 1998). The population consisted of patients with chronic pain including chronic low back pain.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Five of the studies did not report adequate randomization procedures [19,20,40,41], nine did not have adequate allocation concealment [18-20, 23, 24, 29, 31, 39, 41, 44, 46] and none of the studies used assessor blinding (Table 1).…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
“…Seven studies did not state the economic perspective adopted [21, 22, 29-32, 35, 41]. An incremental costeffectiveness analysis was conducted in all but 2 of the 19 cost-effectiveness or cost-utility studies [23,24,41]. Three of the nine studies which had a follow-up period of greater than 1 year did not use discounting [23][24][25]30].…”
Section: Quality Of the Economic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation